AN ANALYSIS OF CHARACTER VALUES IN CHILDREN SONGS: CAN CHILDREN SONGS BE IMPLEMENTED IN THEMATIC LEARNING - Ali Mustadi; Wening Sari; Felinda Nurmalitasari; Armelia Rahmi Lubis; Noormalita Dian (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aimed to provide a general description of children’s song lyrics and to describe the implementation of children’s songs in thematic learning for grades I–III of elementary school. This research employed a content analysis method with a qualitative approach. The data analysis process included: (1) collecting data, (2) selecting samples, (3) recording, (4) reducing, (5) drawing conclusions, and (6) narrating findings. The results revealed that: (1) children’s songs are effective in conveying messages in an enjoyable way; (2) among eight songs analyzed, one contained character values that did not align with the 18 character values taught to students; (3) many positive character values were present in children’s songs, such as religiosity, honesty, responsibility, discipline, independence, environmental care, diligence, and caring for others, which should be instilled in elementary school students, particularly grades I–III; and (4) children’s songs can be effectively integrated into thematic learning, either to begin a lesson, as learning material, or as examples for student assignments.